Penetapan Harga Jual Beli Kambing Perspektif Marketing Syariah - Ahmad Kuzaini; Peni Haryati (edujavare, 2023)
This article discribe and analys the islamic marketing perspective regarding the determination of buying and selling price of goats. The pricing practice studied is the sale andpuschase price of goats which is carried out on the goat farm owned by Mr. Samsudi and the goat farm owned by Mr. Azis. This research is important to do. Researcher found a problem in a trade, namely pricing errorscan lead to serious consequences and effect each other, such as unfair competition. Competition like this cannot be underestimated, because it can hampers the pace of the economy. So we need a good business disipline to overcome them, which can be practiced and provide value for the benefit of businessmen widely, both muslims and non-muslims. This research method uses qualitative data collection techniques in the form of observation, interviews, and documentation. Data alanysis uses reduction, data display, and conclution drawing. Thes the validity of the data using extension of participation, observation persistence, and triangulation. The results showed that the practice of determining prices on Mr. Azis and Mr. Samsudi’s farms was carried out in a negotiable manner while still considering the factors of benefit. Pricing practices applied by the two farms are also in accordance with the values and characteristics of sharia marketing.